2015
DOI: 10.1089/gtmb.2015.0033
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin Gene Polymorphism in an Elderly Sarcopenic Turkish Population

Abstract: MSTN genotyping revealed that only 3.9% (6/152) of participants had the MSTN K153R heterozygous mutation. Despite the detection of this mutation in the study group, no relationship was found between this mutation and sarcopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…3B). Interestingly, this allelic variant was found at higher frequency in two centenarian cohorts, as compared to controls 32 , although the implications of this polymorphism in terms of longevity and maintenance of muscle mass and strength have yet to be definitively established 32-41 . While GDF11 has similar furin and TLD recognition sequences, it is not known if sequence variations, especially in the surrounding areas, which are more divergent, alter furin and/or TLD processing of GDF11 (Fig.…”
Section: Biochemical Regulation Of Gdf11 and Myostatinmentioning
confidence: 94%
See 1 more Smart Citation
“…3B). Interestingly, this allelic variant was found at higher frequency in two centenarian cohorts, as compared to controls 32 , although the implications of this polymorphism in terms of longevity and maintenance of muscle mass and strength have yet to be definitively established 32-41 . While GDF11 has similar furin and TLD recognition sequences, it is not known if sequence variations, especially in the surrounding areas, which are more divergent, alter furin and/or TLD processing of GDF11 (Fig.…”
Section: Biochemical Regulation Of Gdf11 and Myostatinmentioning
confidence: 94%
“…As mentioned above, human genomics studies suggest an association of the K153R polymorphism, thought to increase MSTN activity by enhancing furin processing 31 , with longer lifespan 32 . Interestingly, homozygosity for the K153R allele is extremely rare, and most R allele-carrying centenarians are heterozygous for this variant, a genotype that does not appear to alter muscle phenotypes in aged individuals 38, 39, 41 . Studies in mice also suggest that alterations of MSTN signaling may impact lifespan.…”
Section: Gdf11 Related Pathways In Skeletal Musclementioning
confidence: 99%
“…It is thus possible that individuals carrying favourable gene variants are less susceptible to sarcopenia and hence can maintain independence until later life. To date, five studies have investigated the association of SNPs with sarcopenia; limited to VDR, IL6, ACTN3 and MSTN polymorphisms [19][20][21][22][23] . The studies identified an association of ACTN3 and VDR gene variants with sarcopenia, but did not find any association with IL6 and MSTN variants.…”
mentioning
confidence: 99%
“…Two of the factors that significantly affect the association of MSTN genotypes with muscle mass and skeletal muscle strength are sex and age. Experiments to identify the effect of MSTN on muscle mass and strength showed different results depending on these two factors [ 66 , 67 ].…”
Section: Methodsmentioning
confidence: 99%